EVALUATION OF ANTI-DIABETIC ACTIVITY OF TERMINALIA ARJUNA ROOT EXTRACT IN ALLOXAN INDUCED DIABETIC RATS - Singh, Shikha; Shukla, Neeru; Bhowmick, Mithun; Rathi, Jagdish (Journal of Biomedical and Pharmaceutical Research, 2019)
The present study was carried out to evaluate the effect of root extract  of Terminalia arjuna on blood glucose level of normal and diabetic rats was evaluated in this study. Physicochemical investigations were performed on the acetone extract of Terminalia arjuna (roots). 15-day treatment of extracts associated with reduced the elevated levels of TC, TG as compared to negative control in diabetic animals. The data obtained from this study showed that the treatment of extracts and glibenclamide protects the diabetic rats from massive body weight loss, when given orally, daily for 15 days. Evaluation of anti-diabetic activity of terminalia arjuna showed that the root extract of Terminalia arjuna have potent antidiabetic effects in alloxan-induced diabetic rats.Keywords: Terminalia arjuna, root extract, glibenclamide, alloxan